ETOS KERJA PENGRAJIN KERUPUK SAGU DI DESA PULAU KIJANG KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Ningsih, Witra; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Kijang Island Village, Kuantan Hilir Subdistrict, Kuantan Singingi Regency by qualitative method on six research subjects. Data was collected by in-depth interviews. The aim of the study was to determine the profile and work ethic of sago cracker craftsmen. The results showed that the profile of sago cracker craftsmen has characteristics, namely low education, productive age, family dependence of slightly less than three people, average income of 3.7 million per month, average expenditure of 2.8 million per month and average the average length of business is six years. The ethos of sago cracker craftsmen seen from discipline in work and work skills is high, while morale and motivation are moderate.Keywords: Work Ethics, Craftsmen